Silence of miR-32-5p promotes endothelial cell viability by targeting KLF2 and serves as a diagnostic biomarker of acute myocardial infarction - Yunxiang Dai; Tingguo Yan; Yuming Gao (BMC, 2020)
Abstract Background MicroRNAs (miRNAs) have been investigated in various cardiovascular diseases. As a fatal disease, acute myocardial infarction (AMI) is a serious global health burden. The purpose of this study was to investigate the role of miR-32-5p in AMI patients and human umbilical vein endothelial cells (HUVECs) to explore novel diagnostic and therapeutic approaches for AMI. Methods A target prediction tool miRanda and the luciferase activity assay were used to confirm the interaction of miR-32-5p with Kruppel-like factor 2 (KLF2). Effect of miR-32-5p on HUVECs viability was examined using CCK-8 assay. Serum miR-32-5p expression was measured using quantitative Real-Time PCR, and its correlation with myocardial damage and endothelial injury markers and pro-inflammatory cytokines was assessed. Receiver operating characteristic (ROC) curves were used to evaluate the diagnostic value of miR-32-5p in AMI patients. Results miR-32-5p, as a direct regulator of KLF2, could suppress the cell proliferation of HUVECs. Serum miR-32-5p expression was elevated in AMI patients and positively correlated with the biomarker levels of myocardial damage and endothelial injury and pro-inflammatory cytokines. The area under the ROC curve for miR-32-5p was 0.949, indicating the relatively high diagnostic accuracy of miR-32-5p in AMI patients. Conclusion The data of this study revealed that the increased serum miR-32-5p expression serves as a candidate diagnostic biomarker of AMI, and that miR-32-5p may be involved in the myocardial damage, endothelial injury and inflammatory responses of AMI by targeting KLF2, indicating the potential of miR-32-5p as a diagnostic biomarker and molecular target to improve the treatment of AMI.